Cemetery at Bathurst Inlet, Nunavut -- photograph ... - Seale, Linda N. (University of Alberta Library, 2001)
Cemetery at Bathurst Inlet, Nunavut. The large cross to the right marks a mass grave for victims of an influenza epidemic in 1949. Photographed June 2001 ...